Nociceptive TRP Channels: Sensory Detectors and Transducers in Multiple Pain Pathologies - Aaron D. Mickle; Andrew J. Shepherd; Durga P. Mohapatra (MDPI AG, 2016)
Specialized receptors belonging to the transient receptor potential (TRP) family of ligand-gated ion channels constitute the critical detectors and transducers of pain-causing stimuli. Nociceptive TRP channels are predominantly expressed by distinct subsets of sensory neurons of the peripheral nervous system. Several of these TRP channels are also expressed in neurons of the central nervous system, and in non-neuronal cells that communicate with sensory nerves. Nociceptive TRPs are activated by specific physico-chemical stimuli to provide the excitatory trigger in neurons. In addition, decades of research has identified a large number of immune and neuromodulators as mediators of nociceptive TRP channel activation during injury, inflammatory and other pathological conditions. These findings have led to aggressive targeting of TRP channels for the development of new-generation analgesics. This review summarizes the complex activation and/or modulation of nociceptive TRP channels under pathophysiological conditions, and how these changes underlie acute and chronic pain conditions. Furthermore, development of small-molecule antagonists for several TRP channels as analgesics, and the positive and negative outcomes of these drugs in clinical trials are discussed. Understanding the diverse functional and modulatory properties of nociceptive TRP channels is critical to function-based drug targeting for the development of evidence-based and efficacious new generation analgesics.